Clinical and epidemiological features of leishmaniasis in northwestern-Argentina through a retrospective analysis of recent cases - Garcia Bustos, Maria Fernanda (2015)
Leishmaniasis is a parasitic disease caused by hemoflagellates of the genus Leishmania and is transmitted to humans by the bite of infected phlebotomine sandflies. Depending on the Leishmania species, the disease has different clinical forms including cutaneous, mucocutaneous, and visceral manifestations. Previous studies performed in endemic zones of northwestern-Argentina, during epidemic outbreaks, have been important for detecting patients suffering from the acute phase of the disease, but have not given a complete representation of the clinical and epidemiological features in the region. Furthermore, due to the resurgence of leishmaniasis worldwide and in particular the large increase of international tourism to the region, it seems pertinent to update the current epidemiological and clinical profile of leishmaniasis in northwestern-Argentina. Here we present a retrospective analysis of 95 Leishmania positive cases, presenting between 2000?2014. Patients were derived from hospitals and diagnosed in our lab at the University of Salta, located in a non-endemic area in Salta, Argentina. We detected numerous extensive mucocutaneous cases (34/95, 35.8%) distinct from mucosal affected patients, some instances originating in locations with no previously reported human cases. Additionally patients suffering from concomitant diseases, besides leishmaniasis, were assessed. These included Chagas disease, syphilis, deep mycoses, tuberculosis, toxoplasmosis and intestinal parasitosis. This study updates the clinical and epidemiological features of leishmaniasis in northwestern-Argentina, and discusses the implications and management strategy for patients who acquire the disease in this region.